Kinerja Koperasi Unit Desa Ulun Tanjung Desa Kerobokan, Kecamatan Kuta Utara, Kabupaten Badung (Ditinjau dari Balanced Scorecard) - MARTAULINA SAGALA; MADE ANTARA; WAYAN GINARSA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT Performance Village Unit Cooperative of Ulun Tanjung at Kerobokan Village, District North of Kuta (In terms of Balanced Scorecard) Balanced scorecard is used to balance the effort and attention to financial and non-financial performance,well short-term performance, long-term performance. Research objective is to determine the performance of Village Unit Cooperatives (KUD) Ulun cape with a balanced scorecard is financial perspective, customer perspective, internal business process perspective and learning and growth perspective in 2007 till 2011. The study was conducted in KUD Ulun Cape, Kerobokan village, North Kuta district. Types of data collected quantitative and qualitative data. Collection methods used interviews, observation, literature study. Based on the analysis of the financial perspective used liquidity ratios (current ratio), the solvency ratio (total assets to debt ratio) were considered unfavorable, the profitability ratio (net profit margin) were rated good. Customer perspective with the customer growth rate was still inadequate, level of customer satisfaction members and non members assessed satisfied. Internal business process perspective to manufacturing cycle efficiency savings transaction processing, loan application runs efficiently assessed. Learning and growth perspective the productivity of employees rated well, employee retention experienced twice the velocity. Based on this research, can be suggestion is channeling the funds raised at the business unit in order to be distributed with security, management professionally, while maintaining quality to customers and non-customers. Keywords : Balanced Scorecard, Village Unit Cooperative